Ambient Electrochemical Synthesis of Ammonia from Nitrogen and Water Catalyzed by Flower‐Like Gold Microstructures - Wang, Ziqiang; Li, Yinghao; Yu, Hongjie; Xu, You; Xue, Hairong; Li, Xiaonian; Wang, Hongjing; Wang, Liang (ChemSusChem, 2018)
Electrochemical nitrogen reduction to ammonia is proposed as a promising alternative to the Haber–Bosch process because it can be driven by renewable electricity at ambient conditions. Currently, the development of such a process is hampered by the lack of efficient electrocatalysts for the nitrogen reduction reaction (NRR). Herein, we report a super‐rapid approach for the synthesis of flower‐like Au microstructures (Au flowers) within 5 s. The obtained Au structures are assembled by staggered nanoplates as building blocks, which provide abundant electrocatalytically active sites for the NRR. The Au flowers achieve a high performance (NH3 yield: 25.57 μg h−1 mgcat.−1; faradaic efficiency: 6.05 %), 100 % selectivity (no N2H4 production), and long‐term durability toward the electrochemical ammonia production. The work is highly valuable for the rapid synthesis of active catalysts for the NRR. Flower power! Au flowers have been synthesized by a one‐step approach for electrocatalytic nitrogen reduction to ammonia under ambient conditions (see figure). Au flowers achieve a high NH3 yield (25.57 μg h−1 mgcat.−1), good faraday efficiency (6.05 %), 100 % selectivity and excellent durability toward electrochemical ammonia production.